Chapter Украинская культура Василя Стуса между Европой и Россией - Achilli, Alessandro (Firenze University Press, 2022)
The writings of Vasyl’ Stus (1938-1985) offer an interesting example of some typical dynamics of Ukrainian culture, divided among attraction for Europe and the need to reaffirm its own Europeanness, the autoreferential temptation, and the Russian model – in its turn marked by the Westernism/Slavophilism dichotomy. Stus reflects upon Ukrainian literature in relation to its romantic tradition, European modernism and Russian literature, coming to conclusions that may appear unexpected and paradoxical for an intellectual usually deemed a model of traditional patriotism.